Christianity in Korea - Baker, Donald; Buswell, Robert E.; Buswell, Robert E.; Chang, Paul Yunsik; Chong, Kelly H.; Clark, Donald N.; Grayson, James Huntley; Kang, Wi Jo; Kim, Byong-suh; Kim, Chong Bum; Kim, Wonil; Kwang, Cho; et al. (University of Hawaii Press, 2007)
Despite the significance of Korea in world Christianity and the crucial role Christianity plays in contemporary Korean religious life, the tradition has been little studied in the West. Christianity in Korea seeks to fill this lacuna by providing a wide-ranging overview of the growth and development of Korean Christianity and the implications that development has had for Korean politics, interreligious dialogue, and gender and social issues. The volume begins with an accessibly written overview that traces in broad outline the history and development of Christianity on the peninsula. This is followed by chapters on broad themes, such as the survival of early Korean Catholics in a Neo-Confucian society, relations between Christian churches and colonial authorities during the Japanese occupation, premillennialism, and the theological significance of the division and prospective reunification of Korea. Others look in more detail at individuals and movements, including the story of the female martyr Kollumba Kang Wansuk; the influence of Presbyterianism on the renowned nationalist Ahn Changho; the sociopolitical and theological background of the Minjung Protestant Movement; and the success and challenges of Evangelical Protestantism in Korea. The book concludes with a discussion of how best to encourage a rapprochement between Buddhism and Christianity in Korea